Identification, by a monoclonal antibody, of a 53-kD protein associated with a tubulo-vesicular compartment at the cis-side of the Golgi apparatus (The Rockefeller University Press, 1988)
Purified Golgi membranes of the human intestinal adenocarcinoma cell line Caco-2 were used as an antigen to produce a monoclonal antibody, G1/93, which specifically labels a tubulovesicular compartment near the cis side of the Golgi apparatus, including the first cis-cisterna itself, as visualized by single and double immunoelectron microscopy with antibodies against galactosyltransferase. The antigen recognized by G1/93 was identified as a protein with a subunit size of 53 kD. Pulse-chase experiments revealed that the 53-kD protein dimerizes immediately after synthesis followed by formation of oligomers of approximately 310 kD, probably homohexamers. The protein has a transmembrane topology with only a short cytoplasmic segment as assessed by protease protection experiments. Glycosidase digestion studies indicated that the protein is probably not glycosylated. The unique subcellular distribution of the G1/93 antigen in close vicinity to the cis-Golgi is in line with the notion that this protein may delineate the biosynthetic transport pathway from the endoplasmic reticulum to the Golgi apparatus. Moreover, G1/93 is a useful marker to identify the cis side of the Golgi apparatus in a variety of human cells.